2011
DOI: 10.1016/j.peptides.2011.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of proline position on the antimicrobial mechanism of buforin II

Abstract: Buforin II (BF2) is a histone-derived antimicrobial peptide that causes cell death by translocating across membranes and interacting with nucleic acids. It contains one proline residue critical for its function. Previous research found that mutations replacing proline lead to decreased membrane translocation and antimicrobial activity as well as increased membrane permeabilization. This study further investigates the role of proline in BF2’s antimicrobial mechanism by considering the effect of changing proline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 39 publications
(69 reference statements)
3
64
0
Order By: Relevance
“…For example, considering membrane translocation and DNA binding led to a more complete interpretation how proline mutants affect activity of BF2 [39]. Although AMPs are often characterized as primarily killing bacteria by either permeabilizing membranes or interacting with an intracellular component, several studies have proposed that at least some peptides may function through a combination of these different mechanisms [19, 23, 49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, considering membrane translocation and DNA binding led to a more complete interpretation how proline mutants affect activity of BF2 [39]. Although AMPs are often characterized as primarily killing bacteria by either permeabilizing membranes or interacting with an intracellular component, several studies have proposed that at least some peptides may function through a combination of these different mechanisms [19, 23, 49].…”
Section: Discussionmentioning
confidence: 99%
“…A fluorescent intercalator displacement (FID) assay was used to experimentally measure the relative DNA binding of each peptide [37, 38]. The FID assay, which has been used previously to measure relative DNA binding of HDAPs [9, 39], involved loading of thiazole orange (0.55 μM), an intercalator that fluoresces upon binding double-stranded nucleic acids, in STE buffer (10 mM Tris, 50 mM NaCl, 1 mM EDTA, pH 8.0) into a quartz cuvette. Fluorescence was measured with 509 nm excitation and 527 nm emission and normalized to 0% relative fluorescence.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the positively charged residues in the α-helical sequence, and Arg-rich peptide, associate with the lipid phosphate groups to neutralize the Arg residue and allow the peptide translocation across the membrane (Amand et al 2008; Boman 1995; Su et al 2009). Recently, a report by Xie et al (2011) suggested that the position of Pro residue in buforin II was more important than the overall α-helical content for the translocation (Xie et al 2011). Consistent with these previous reports, YD1 AMP, a positively charged peptide, contains 3 glycines ([G 4,7,10 ]) and 2 proline ([P 2,8 ]) residues out of 10 amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 notes how these sequences compare to the physiological sequences of hipposin, buforin I (BF1), buforin II (BF2) and parasin. Notably, the HipB region that was analogous to buforin II (BF2) included the F10W mutation that has been widely used in previous studies and shown to have analogous properties to the wildtype peptide [15, 16, 18, 20, 21]. …”
Section: 0 Materials and Methodsmentioning
confidence: 99%